A New Cephalaria (Caprifoliaceae) Species from Turkey - Göktürk, Ramazan Süleyman; Yüceol, Fulya; Galatali Seli̇n; Kaya, Ergun; Hamzaoğlu Ergi̇n; Koç, Murat (Phytotaxa, 2023)
Cephalaria saldaensis, collected from Eşeler Mountain around Salda Lake (Yeşilova-Burdur), one of Turkey’s important tourism regions, is described from South-West Anatolia as a new species. Diagnostic morphological and molecular characters from closely similar taxa are discussed. The geographical distribution of the new species and other related species is mapped. Taxonomic comments such as descriptive and diagnostic characters, distribution and ecology, conservation status for this new species are given in the current study. In this study, morphological characterization of three different Cephalaria spp. was also supported via molecular characterization based on PCR technology. Twenty-two ISSR primers were tested using a total of fifteen individuals belonging to three different Cephalaria spp. Five of these primers gave the most productive band profile. A total of 53 bands ranging from 250bp to 2000bp were obtained from the PCR products on agarose gel image, and the polymorphism calculated on the basis of the band profiles was 77.4%. The band profiles were also analyzed using the PopGen32 Software program. The constructed phylogenetic tree grouped the Cephalaria spp. individuals belonging to these three species into two main clusters and the phylogenetic analysis indicated that C. saldaensis was clearly different from the C. scoparia and C. dirmilensis.